2022
DOI: 10.1186/s41938-022-00564-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of isolated entomopathogenic fungus from Egyptian soil against the black cutworm larvae of Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae)

Abstract: Background The black cutworm, Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae), is considered as one of the most destructive pests of many field crops in Egypt. Entomopathogenic fungi (EPF) have long been accepted as relatively safe alternatives to chemical insecticides. In the past decades, many researchers have compared the effective local isolates of EPF to the formulated product of the same fungus and reported that local isolates were more efficient than formulations when used against ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The pathogenicity of two entomopathogenic fungi was observed on larvae of A. ipsilon, the formation of white spores indicated the growth of B. bassiana at LC50 (2 10 8 spore/ml) after 7 days, the formation of green spore after 15 days at LC50 (1.9 10 8 spore/ml) on the cadaver of larval pupal intermediate indicated the growth of M. anisopliae (Gabarty et al, 2014). Similarly, the Entomopathogenic Fungi (EPFs), Beauveria bassiana isolates were evaluated against the last instar larvae of A. ipsilon, and after 14 days (48 and 100%) mortality was observed at concentrations of 9.2 × 10 4 and 2.9 × 10 6 spores/ ml, respectively (Ahmed et al, 2022).…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…The pathogenicity of two entomopathogenic fungi was observed on larvae of A. ipsilon, the formation of white spores indicated the growth of B. bassiana at LC50 (2 10 8 spore/ml) after 7 days, the formation of green spore after 15 days at LC50 (1.9 10 8 spore/ml) on the cadaver of larval pupal intermediate indicated the growth of M. anisopliae (Gabarty et al, 2014). Similarly, the Entomopathogenic Fungi (EPFs), Beauveria bassiana isolates were evaluated against the last instar larvae of A. ipsilon, and after 14 days (48 and 100%) mortality was observed at concentrations of 9.2 × 10 4 and 2.9 × 10 6 spores/ ml, respectively (Ahmed et al, 2022).…”
Section: Entomopathogenic Fungimentioning
confidence: 99%
“…This moth can fly thousands of kilometers under suitable conditions expanding its distribution range (Liu et al, 2015(Liu et al, , 2016Liu, 2015;Hayat et al, 2021;Lee et al, 2023), besides its considerable reproductive capacity Shield, 1998, Mishra, 2020). It is a polyphagous insect known to feed on several vegetables and many economically important grains worldwide (Navarro et al, 2010;Fernandes et al, 2013;Picimbon, 2020;Rodingpuia and Lalthanzara, 2021;Ahmed et al, 2022). Some control practices are usually applied for controlling A. ipsilon, such as cultural control (Bajwa and Kogan, 2004;Guedes and Picanço, 2012), mechanical control (Manishkumaret al, 2020), physical control (Abd El-Hamid, 2004Ali, 2011;Mohamed, 2012), host-plant resistance (Richmond and Shetlar, 2001;Hussaini et al, 2003a, b) and biological control (Viji and Bhagat, 2001;Salehi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some control practices are usually applied for controlling A. ipsilon, such as cultural control (Bajwa and Kogan, 2004;Guedes and Picanço, 2012), mechanical control (Manishkumaret al, 2020), physical control (Abd El-Hamid, 2004Ali, 2011;Mohamed, 2012), host-plant resistance (Richmond and Shetlar, 2001;Hussaini et al, 2003a, b) and biological control (Viji and Bhagat, 2001;Salehi et al, 2005). However, the control strategy of A. ipsilon depends mainly on the application of synthetic insecticides (Shakur et al, 2007;Abd El-Aziz et al, 2019;Veres et al, 2020;Ismail, 2021), to which this pest quickly develops resistance and cross-resistance (Fahmy, 2014;Mahmoud et al, 2016;Ahmed et al, 2022). Also, chemical insecticides are often not effective and remain inadequate for the control of A. ipsilon because of its larval hiding behavior during the daylight hours causing hidden damage in the fields (Capinera, 2001;Takeda, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi isolation involving the use of selective media methods is apparently the most common. Meanwhile, several insect-baiting methods have also been widely reported as effective for the isolation of entomopathogenic fungal species [ 4 , 18 , 19 , 20 , 21 , 22 ]. Some of these aforementioned studies as well as few other RIFA-related studies have revealed that several generalists and entomopathogenic fungi occur in fire ants mounds [ 7 , 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%